A Case Study on the Use of Wordwall as A Formative Assessment Tool in Informatics Learning - Ii Pratiwi; Jumiati Siska; Imma Rachayu (Jurnal Komputer Indonesia, 2026)
This study aims to describe the implementation of Wordwall as a formative assessment tool and analyze the transformation of student responses in Informatics learning at SMP Negeri 8 Bengkulu. The research methodology employed is qualitative with a case study design. The researcher serves as the key instrument, collecting data through limited participant observation, semi-structured interviews with teachers and students, and field notes. Data analysis techniques follow the Miles and Huberman model, while data validity is ensured through source and technique triangulation based on Moleong's theory. The results indicate that the use of Wordwall successfully transformed the classroom atmosphere from passive to interactive compared to conventional methods. Gamification features and instant feedback significantly increased student enthusiasm and independence in completing evaluations. Although this study is qualitative, supporting data shows an increase in average scores from 5.41 on written tests to 7.83 when using Wordwall. In conclusion, Wordwall is effectively used as a formative assessment medium capable of providing an enjoyable learning experience while facilitating teachers in automatic grade processing. Suggestions for educators include optimizing the variety of features within Wordwall and ensuring the readiness of digital infrastructure to support the sustainability of interactive assessment.